Diet Of Peary Caribou, Banks Island, N.W.T. - Shank, Christopher C.; Wilkinson, Paul F.; Penner, David F. (ARCTIC, 1978)
The results of analyses of rumen contents from 101 Peary caribou (Rangifer tarandus pearyi J. A. Allen 1902) collected on Banks Island are presented. Peary caribou on Banks Island were found to be versatile, broad spectrum grazers specializing on upland monocots, to ingest few lichens, and to exhibit significant seasonal and/or regional differences in diet.